Appraisal of Ethiopian Tax Dispute Resolution System at the Review Department (of the Ministry of Revenue) and at Federal Tax Appeal Commission - Silesh, Gizachew; Chane, Gizachew Silesh; Tadesse, Yibekal; Woldekidan, Israel (Bahir Dar University Journal of Law, 2023)
Tax disputes are inherent parts of a tax system, and require resolution mechanisms that effectively regulate and protect the interest of disputing parties. Commonly, countries provide for several layers of dispute resolution schemes. The schemes comprise internal review and external dispute resolution mechanisms that include quasi-judicial tax tribunals, courts and different kinds of Alternative Dispute Resolution methods. Ethiopia has made successive reforms on the laws and institutions pertaining to taxation and tax dispute resolution procedures. Despite successive reforms in the substantive content of tax laws, the dispute resolution system by and large remained the same. The 2016 reform, one of the latest reform moves, maintained much of the dispute resolution institutions with some changes in the details. The failure or success associated with these reforms and the overall application of tax dispute resolution system in the country has not been sufficiently studied. Using a qualitative research approach, this research thoroughly examined the Ethiopian law and the practice pertaining to the prevailing tax dispute resolutions system at Review Department of the Ministry of Revenue and the Federal Tax Appeal Commission. The research found out several legal and practical limitations regarding geographical accessibility, independence, legal certainty and access to justice. Thus, the existing tax dispute resolution system of Ethiopia needs to be re-visited so that the Country will have a tax dispute resolution system that balances the interest of the public and taxpayers.